Penerapan Nilai-Nilai Kristiani Dalam Lingkungan Masyarakat Heterogen - Pinondang Simanjuntak; Hanna Dewi Aritonang (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Ngabang, 2024)
The importance of applying Christian values is very necessary in improving social harmony. Because our country is a country that has many differences in ethnicity, race, culture, language, and religion. With these differences, it triggers conflicts and disputes. As has happened recently, there have been many rejections of minority individuals. This happened in high school, where there was rejection at school. And not only in certain schools, but also in churches that interfere in politics. Therefore, we need to maintain Christian values for the harmony and integrity of our country.